P133 Inter-speciality working to provide competencies in genital dermatology for GUM trainees. (30th June 2016) - Colver, Helen; Harman, Karen
Abstract : Background: The Health and Social Care Act (2012) led to decommissioning of genital dermatology services in our sexual health clinic, creating a training deficiency in this aspect of the GUM curriculum. Objective: To develop a service for patients with vulval pathology whilst also providing competencies in genital dermatology for GUM trainees. Methods: Training concerns were discussed with the local Health Education England board. A dermatology consultant with considerable experience in vulval disorders agreed to supervise a weekly vulval clinic, held within the dermatology department, to which GUM trainees would be seconded. Women were seen by a GUM trainee under the supervision of the dermatology consultant. Details of patient outcomes were prospectively recorded. Results: Over 10 months 84 women were seen in a total of 165 visits. The patients had a median age of 57 (range 19–94) years. 34 (40.5%) were follow-up dermatology patients. Of the 50 remaining patients, 10 (20%) were referred from other dermatology consultants, 3 (6%) from gynaecology, 8 (16%) from genitourinary medicine, and 29 (58%) from general practice. Diagnoses are tabulated below. Discussion: Inter-speciality working has allowed GUM trainees to develop expertise in genital dermatology whilst the presence of a GUM doctor facilitates exploration of psychosexual issues in these patients. We recommend that other centres consider this model for training and service provision.